Significantly different noun-verb distinguishing mechanisms in written Chinese and Chinese sign language: An event-related potential study of bilingual native signers - Xu, Lewen; Gong, Tao; Shuai, Lan; Feng, Jun (Frontiers in Neuroscience, 2022)
Little is known about: (a) whether bilingual signers possess dissociated neural mechanisms for noun and verb processing in written language (just like native non-signers), or they utilize similar neural mechanisms for those processing (due to general lack of part-of-speech in sign languages); and (b) whether learning a language from another modality (L2) influences corresponding neural mechanism of L1. In order to address these issues, we conducted an electroencephalogram (EEG) based reading comprehension study on bimodal bilinguals, namely Chinese native deaf signers, whose L1 is Chinese Sign Language and L2 is written Chinese. Analyses identified significantly dissociated neural mechanisms in the bilingual signers’ written noun and verb processing (which also became more explicit along with increase in their written Chinese understanding levels), but not in their understanding of verbal and nominal meanings in Chinese Sign Language. These findings reveal relevance between modality-based linguistic features and processing mechanisms, which suggests that: processing modality-based features of a language is unlikely affected by learning another language in a different modality; and cross-modal language transfer is subject to modal constraints rather than explicit linguistic features.